Creating a clinical platform for carbon‐13 studies using the sodium‐23 and proton resonances - Grist, JT; Hansen, ESS; Sánchez‐Heredia, JD; McLean, MA; Tougaard, R; Riemer, F; Schulte, RF; Kaggie, JD; Ardenkjaer‐Larsen, JH; Laustsen, C; Gallagher, FA (Wiley, 2020)
Purpose Calibration of hyperpolarized 13C‐MRI is limited by the low signal from endogenous carbon‐containing molecules and consequently requires 13C‐enriched external phantoms. This study investigated the feasibility of using either 23Na‐MRI or 1H‐MRI to calibrate the 13C excitation.